OP X – 4 Multipollutant models for assessing particle number concentration exposure and changes in glucose metabolism in the heinz nixdorf recall study. (18th March 2018) - Lucht, Sarah; Hennig, Frauke; Matthiessen, Clara; Ohlwein, Simone; Icks, Andrea; Jakobs, Hermann; Moebus, Susanne; Jöckel, Karl-Heinz; Hoffmann, Barbara
Abstract : Background/aim: Prior studies have shown possible links between medium-term air pollution (AP) exposure and glucose metabolism markers. We investigated whether associations between accumulation mode particle number concentration (PNAM ) and glucose metabolism measures are robust to adjustment for other potential co-pollutants. Methods: This analysis included observations from non-diabetic participants (nobs =7, 108) of the population-based Heinz Nixdorf Recall study at baseline (2000–2003) and follow-up examination (2006–2008). Particulate matter (PM), accumulation mode particle number (PNAM ), and NO2 exposures were estimated for each examination at every participant's residence using the spatiotemporal EURopean Air pollution Dispersion (EURAD) chemistry transport model. Associations between a range of short- and medium-term PNAM exposures (1- to 182 day average prior to blood draw) and glucose metabolism measures (blood glucose, HbA1c) were assessed for robustness to co-adjustment for PM2.5, PM10, and NO2 using a mixed effects linear regression model Results: PNAM exposure showed low to medium correlation with PM2.5, PM10, and NO2 (e.g., 0.33–0.53 for 28 day exposures). In the model with only PNAM and blood glucose, associations were seen for 14- to 91 day mean exposures windows with strongest associations observed for the 60 day window (1.05 mg/dL per 1580 n/mL (95% CI: 0.46 to 1.63)). Co-adjustment for PM2.5 attenuated associations at all time points (e.g., 0.67 mg/dL per 1580 n/mL (95% CI: −0.22 to 1.55) for the 60 day window) whereas associations for PNAM remained largely unchanged upon adjustment for PM10 and NO2 . For HbA1c, strongest associations were apparent for the 105 day exposure window (0.096 p.p. per 1257 n/mL (95% CI: 0.075 to 0.116)). HbA1c model estimates were largely unchanged upon adjustment for co-pollutants. Conclusion: The associations between exposure to PNAM and glucose metabolism measures were robust to adjustment for co-pollutants, possibly suggesting that exposure to small particles plays an independent role in influencing glucose regulation.